[Afisz. Incipit] Odezwa do wszystkich Z.M.P-ców i S.P-ców! (Lębork : [wydawca nieznany], 1949)
Afisz wzywający do wzięcia udziału w żniwach.
Keywords: Lębork (Polska) -- 1945-1970 -- druki ulotne; Lębork (Polska) -- 1945-1970 -- źródła